Public Policies of Environmental Education in Brazil: An overview from international and national events (Research, Society and Development, 2021)
This study presents an analytical review of the Public Policy Agenda of Environmental Education  in Brazil from international and national events. It aims to present and list the contributions to the formulation, insertion and implementation of these for formal education, non-formal and informal. Methodologically, it is a qualitative research with documentary analysis and interpretative nature from the environmental problem that became effective agenda for Public Policy from the second half of the twentieth century. It was observed that the agenda of Environmental Education in Brazil is in constant transformations, (re)formulations and (re)construction which infers that Environmental Education as dimension of education has an important force for the process of sensitization and awareness in relations that emerge between man, society and nature.